TEACHERS’ EXPERIENCES REFLECTED IN THEIR TEACHING OF DESCRIPTIVE TEXT TO GRADE VIII STUDENTS OF SMPN 2 MEDAN - Septian Wahyu Maulana; Berlin Sibarani (Universitas Negeri Medan, 2021)
The study was aimed to see whether teachers’ experiences are reflected in teaching descriptive text to grade VIII students of SMPN 2 Medan or not. This study was conducted by using descriptive qualitative method through a collection of techniques used to specify, delineate, or describe naturally occurring phenomena without experimental manipulation. The data were gathered by administering interview to three English teachers with different years of experience and observing their teaching of descriptive text during a classroom session. The observation and interview result proved that the three English teachers did not reflect their teaching experience when teaching descriptive text to the students. The reason why the three English teach descriptive text in the ways they do varied from one to the other.Keywords: Experience, Descriptive Text, Qualitative Descriptive Research